Non-Fermi Liquid Properties in a Cubic Pr-Based Compound PrPb3 under Magnetic Fields. (January 2016) - Yoshida, T; Machida, Y; Izawa, K; Onimaru, T; Suzuki, H S
Abstract: We have studied the electrical resistivity ρ of the Pr-based cubic compound PrPb3 with the Γ3 doublet ground state. The temperature dependence of the resistivity is found to exhibit a non-Fermi liquid behavior with convex curve at high temperatures, as suggestive of the putative realization of the quadrupole Kondo effect. At low temperatures under magnetic fields, we observe anomalies associated with antiferroquadrupole (AFQ) ordering, incommensurate/commensurate transition inside the AFQ phase, and field-induced phase transition. The constructed phase diagram based on these observations well reproduces the one determined by the specific heat and magnetization measurements. Deep inside each phase, the resistivity turns to show the Fermi liquid behavior with the quadratic temperature dependence. The estimated slope of the T 2 term is almost independent of field in contrast to our previous work of PrIr2 Zn20 and PrRh2 Zn20 in which the slope is largely enhanced at the edge of the AFQ phase.